Coding with minecraft :|the development of middle school students’ computational thinking - Kutay, Emine. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
The purpose of this study is to examine the role of Minecraft-based coding activities on computational thinking (CT) of middle school students. In the study, CT is conceptualized so that it encapsulates not only the knowledge of CT concepts but also the use of CT practices. In this regard, the study employed one group pre-test post-test design, supported with qualitative data. Data were collected using a combination of CT concept knowledge tests, the Minecraft-based computational artifacts, and artifact-based interviews. The participants were 5th-grade middle school students (n = 11 female and n = 9 male) at a public school in Istanbul who had no formal coding experiences prior to the study. The Minecraft-based coding activities were designed and implemented as an instructional program to last six weeks. Students were pre-tested before attending in the program. After participating in weekly lessons consisting of Minecraft-based coding activities, students were post-tested and interviewed. The results showed a statistically significant increase in students’ knowledge of CT concepts after participating in the Minecraft-based coding activities. The analysis also showed that there were no statistically significant differences between students’ scores in terms of gender. Based on the analysis of Minecraft projects, the concepts of variables, operators, and conditionals appeared to be the least used concepts, while students mostly made use of loops and events in their computational artifacts. In terms of the qualitative analysis of artifact-based interviews, students displayed CT practices of experimenting and iterating, testing and debugging, reusing and remixing, and abstracting and modularizing.
Keywords: Minecraft (Game)